Students’ perceptions towards business ethics - Mhd. Sarif, Suhaimi (2010)
Business Ethics is one of university required courses for students of Kulliyyah of Economics and Management Sciences, IIUM. Since the course is compulsory, students have no other options. The study aims to evaluate the perceptions of current Business Ethics students towards Business Ethics whether they will enroll in this subject if it is just an elective course. An opinion survey with 109 Business Ethics students showed that 105 students (96%) will enroll into this course even in the case the subject is reclassified as an elective course. Moreover, almost all respondents have a very good knowledge about the importance of ethics in life and business. Academically, they believed by studying Business Ethics formally, they can acquire knowledge about ethics from various perspectives and sources through assignments and examinations. Such exposure will help them to make sound, ethical and value added decisions for personal as well as for others. However, four respondents have decided not to enroll in this subject because they believed that ethics can be learnt through experience and action oriented. In addition, ethical values are derived from personal values. For future research, the study should be extended to former Business Ethics who used to learn the course to validate the opinions of current Business Ethics students. Moreover, the future study also should obtain views from the course instructors of Business Ethics of all public universities in Malaysia.